The development of guidelines for the design and evaluation of warning signs for young children - Patrick Waterson; Alice Monk (2013)
We report a study which aimed to provide further development and refinement of a set of guidelines (Waterson et al., 2012) for the design and evaluation of warning signs and other visual material for young children (i.e., aged 5–11 years). The study involved a set of semi-structured interviews and focus groups with the parents of young children, teachers, human factors experts and other groups (n = 38). The findings from the study provided broad support for the guidelines, as well as highlighting a number of issues which need to be addressed. These included the need to consider the target audience in more detail and provide additional guidance covering possible tie-ins with safety campaigns, sign location, age differences, gender and children's special needs. Similar findings were obtained with regard to the evaluation guidelines and their coverage of methods and activities for testing signs (e.g., simulation, role playing). We discuss our findings within the context of a revised set of guidelines and a set of suggestions aimed at working towards a more comprehensive approach to the design/evaluation of signs for young children. The paper concludes with a set of future topics for research including a discussion of ways forward in terms of improving support for design and evaluation including behavioural testing with children, their parents and other care givers.